2014
DOI: 10.1371/journal.pone.0106350
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Access to Emotions: Neural Signature of EMDR Stimulation

Abstract: BackgroundEye Movement Desensitisation and Reprocessing (EMDR) is a method in psychotherapy effective in treating symptoms of posttraumatic stress disorder. The client attends to alternating bilateral visual, auditory or sensory stimulation while confronted with emotionally disturbing material. It is thought that the bilateral stimulation as a specific element of EMDR facilitates accessing and processing of negative material while presumably creating new associative links. We hypothesized that the putatively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
2
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 55 publications
(65 reference statements)
9
39
2
6
Order By: Relevance
“…Specifically, decreased amygdala activity has been found after individual trauma-focused psychotherapy (Felmingham et al, 2007; Peres et al, 2007, 2011) and decreased insula activity after individual and group trauma-focused cognitive (behavioral) treatment (Peres et al, 2007, 2011; Thomaes et al, 2012). However, our findings are at odds with the findings from a previous study in healthy controls, showing that bilateral alternating stimulation resulted in increased amygdala activity and decreased DLPFC activity (Herkt et al, 2014). The difference with our study, apart from the study population, is that Herkt et al (2014) used general disgusting visual stimuli instead of personal traumatic audio-scripts.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Specifically, decreased amygdala activity has been found after individual trauma-focused psychotherapy (Felmingham et al, 2007; Peres et al, 2007, 2011) and decreased insula activity after individual and group trauma-focused cognitive (behavioral) treatment (Peres et al, 2007, 2011; Thomaes et al, 2012). However, our findings are at odds with the findings from a previous study in healthy controls, showing that bilateral alternating stimulation resulted in increased amygdala activity and decreased DLPFC activity (Herkt et al, 2014). The difference with our study, apart from the study population, is that Herkt et al (2014) used general disgusting visual stimuli instead of personal traumatic audio-scripts.…”
Section: Discussioncontrasting
confidence: 99%
“…In a functional magnetic resonance imaging (fMRI) study in 22 healthy controls, it was found that bilateral alternating auditory stimulation while viewing disgusting pictures resulted in increased amygdala activity and decreased DLPFC activity (Herkt et al, 2014). In patients, no such experimental studies yet exist.…”
mentioning
confidence: 99%
“…As attention typically amplifies neuronal responses evoked by task-relevant stimuli, while attenuating responses to irrelevant distractors (Béhuret et al, 2013), it seems likely that the bilaterality of the DAS/BLS would amplify the SR effect more than a constant, nonalternating stimulus. This is what appears to have been observed by Herkt et al (2014) when they compared three groups: bilateral alternating stimulation in the form of auditory tones, bilateral simultaneous auditory tones, and no additional stimulation. The results show that the effects for alternating BLS were greater than those for simultaneous BLS, which was in turn greater than no additional stimulation (Herkt et al, 2014).…”
Section: The Issue Of Bilateralitysupporting
confidence: 73%
“…This is what appears to have been observed by Herkt et al (2014) when they compared three groups: bilateral alternating stimulation in the form of auditory tones, bilateral simultaneous auditory tones, and no additional stimulation. The results show that the effects for alternating BLS were greater than those for simultaneous BLS, which was in turn greater than no additional stimulation (Herkt et al, 2014). This is consistent with the modeling that views increased thalamic activity as facilitating the repair and integration of somatosensory, memorial, cognitive, and synchronized hemispheric functions.…”
Section: The Issue Of Bilateralitysupporting
confidence: 73%
“…To objectively explore the physiological effects of EMDR, functional imaging techniques, such as nuclear imaging [5], electroencephalography (EEG)[6], and functional Magnetic Resonance Imaging [7], have been exploited. Modifications in the patterns of cerebral activity have been evidenced, particularly in those brain regions involved in stress management: the so-called hypothalamus-pituitary-adrenal (HPA) axis (an articulated response network to a stressful condition which involves deep brain regions, such as hypothalamus and amygdala) and cortical areas, such as the prefrontal cortex (PFC) [8].…”
Section: Introductionmentioning
confidence: 99%